2020
DOI: 10.2174/1875399x02013010114
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ketogenic Diet on Body Composition during Resistance Training among Untrained Individuals

Abstract: Background: Resistance training (RT) has been established as the most efficient approach for lean body mass maintenance required for preserving a sufficiently high metabolism during weight loss. Objective: This study aimed to evaluate the impacts of the ketogenic diet (KD) and regular diet (RE) in combination with 8-week resistance exercise (RT), on body weight, body fat mass (BFM), and lean b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…The difference in the magnitude of these changes could be altered, in part, by the different caloric intake strategies between studies and the amplitude of the restriction in the intake of CH (Table 1). This may explain that studies with daily calorie restriction of CH lower than 5% reported greater losses of fat mass (16,22,29). Nonetheless, these data provide strong evidence that combining LCHF dietary strategies with regular resistance training can help you lose body weight, with the same guarantees as any other proven nutritional planning (3,21).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The difference in the magnitude of these changes could be altered, in part, by the different caloric intake strategies between studies and the amplitude of the restriction in the intake of CH (Table 1). This may explain that studies with daily calorie restriction of CH lower than 5% reported greater losses of fat mass (16,22,29). Nonetheless, these data provide strong evidence that combining LCHF dietary strategies with regular resistance training can help you lose body weight, with the same guarantees as any other proven nutritional planning (3,21).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in 6 of the studies that analyzed anthropometric parameters, FFM was not monitored, or no significant effects were observed. In the remaining 5 articles, significant decreases in FFM were identified, averaging a value of 22.88% (8,11,16,18,46).…”
Section: Anthropometrical Parametersmentioning
confidence: 99%
See 3 more Smart Citations